Internalisasi Nilai-Nilai Agama Melalui Penciptaan Suasana Keagamaan Di Lingkungan MI Muhammadiyah Tempurrejo Ngawi - Bermi, Wibawati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Madrasah as the institution of Islamic education has a big responsibility to fullfill a religious values ​​to the students until the students have a strong personality for preventing the negative effects of global phenomenon this time. Demoralized issues is demanding for madrasah returns to the religious culture or Islamic culture as based moral of guiding to create a conducive environment for education. There for Academic community of madarasah is a Muslim community that required to internalize Islamic values ​​in all aspects of life. In other word, the Head of Madrasah realizes that the creation of atmosphere reigion in the Madrasah environment was not a simple problem to be realized. Based on the background, then the research problem in this research can be formulated with the following problem formulation: 1) How is the principal strategy madarasah in the creation of religious atmosphere in MIM Tempurrejo Ngawi, 2) How to form a religious atmosphere in MIN Tempurrejo Ngawi. And starting from the formulation of the problem then this research aims for: 1) knowing the head master of madrasah’ strategy for creating thes religious atmosphere in the environment MIN Tempurrejo Ngawi, 2) To describe the form of religious atmosphere in the environment MIN Tempurrejo Ngawi. In accordance the issues of this study, the type of research is qualitative research with rationalistic approach. And then the data is collected by using three approaches, namely: observation, in-depth interviews, and documentation. The result of the datas analysis can be concluded by researcher that three strategies for creating a religious atmosphere in the environment of Madrasah Ibtidaiyah Muhammadiyah Tempurrejo Ngawi are: 1) Improving the quality of employees and teachers, 2) Providing role for teachers and employees to take a part and activate the program and also have a sense of responsibility for creating religious atmosphere in institution, 3) Improving the facilities which are related to the creation of a religious atmosphere. The form of religious atmosphere in the Madrasah Ibtidaiyah Muhammadiyah Tempurrejo Ngawi can be divided into three forms: a) Physical form, that is the whole physical building to support the creation of religious atmosphere, b) The activities, those are the all of religious activities in MIM Tempurrejo Ngawi for instance: Tartil Al-Qur'an, Dhuha prayer, jama’ah of Dhuhur prayer, Friday prayers, Friday clean, commemoration of Islamic days, spending the night of Romadlon, and c) implementing attitude and implementing behavior, those are the whole attitude and behavior that shown by teacher , employees and students in the environment of madrasah such as: Islamic reciprocity, mutual help, mutual visits, mutual respect, mutual respect to the personality such as: friendly, keeping smile, dressing neatly, trusted and disciplined.